Slum Upgrading: The Muungano Wa Wanavijiji (MWW) Vision - (:unkn) unknown (My University, 2011)
This article explores the concept of slum upgrading as understood by Muungano wa Wanavijiji (MWW), a federation of slum dwellers in Nairobi (hereafter referred to as Muungano). It discusses different issues related to slum upgrading projects in Nairobi in two ways: through a description of what slum upgrading means to Muungano and through an interview with Ezekiel Rema, Chairman of Muungano and one of the eighteen founding members of this federation in 1996, who shares the various aspects of Muungano's activities and experiences in the slum upgrading process. In conclusion, the article presents some lessons and recommendations, as suggested by Mr. Rema, on how to achieve a veritable slum upgrading.
Keywords: African Research